PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY TERHADAP PRESTASI BELAJAR SISWA PADA MATERI GERAK DI KELAS VII SMP NEGERI 1 PUCUK - Heny Ekawati Haryono (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
Teacher - center method more widely used in the learning process but knowledge gained students less than the maximum. Therefore, The researcher intended to carry out the process of learning that guides the students discover the concept through their own behavior so that the results are more meaningful and is expected to increase the achievement. This research aimed to describe the effect of the application of Guided Discovery model to the students’ achievement, both affective (scientific attitude), psychomotor, and cognitive, as well as to determine the linkages between these aspects. This research was designed using